Membrane Reactors 2010
DOI: 10.1002/9783527629725.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis and Reaction Kinetics of a Model Reaction

Abstract: The development of new and the improvement of existing reactor concepts is diffi cult without understanding the reaction mechanism and -if a catalyst is used -its operation principles. In the ideal case an accurate kinetic model with detailed structure -activity relations would be available. However, in industrial practice in general only simplifi ed strategies are applied in order to minimize experimental effort and to reduce the complexity of the corresponding mathematical expressions. Often simplifi ed kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The widening of the two bands of graphite has been recurrently observed when the degree of disorder of its structure augments because of an amorphization of the graphite structure. Nevertheless, both the D- and G -bands result from vibration of the sp 2 sites of the carbon–carbon structure; more specifically, the D -band is caused by breathing modes of sp 2 atoms in rings and G -band is the product of the stretching of pairs of the sp 2 atoms in both rings and chains …”
Section: Resultsmentioning
confidence: 99%
“…The widening of the two bands of graphite has been recurrently observed when the degree of disorder of its structure augments because of an amorphization of the graphite structure. Nevertheless, both the D- and G -bands result from vibration of the sp 2 sites of the carbon–carbon structure; more specifically, the D -band is caused by breathing modes of sp 2 atoms in rings and G -band is the product of the stretching of pairs of the sp 2 atoms in both rings and chains …”
Section: Resultsmentioning
confidence: 99%
“…The reduction can be attributed to the weakening of the vanadyl group, which is caused by the significant interaction of vanadium species with cerium species. 27 Meanwhile, the new peak shifts towards higher temperature with the rise of V 2 O 5 loading. This can be explained by the fact that with the rise of V 2 O 5 loading, more surface vanadium atoms interact with the internal vanadium layer and increase the bond strength of the vanadyl group.…”
Section: Reductive Properties Of Catalystsmentioning
confidence: 96%
“…Recent studies of Klose et al, however, suggested a new structural model for vanadium surface species on alumina supported vanadium catalysts [42]. In their work a trimeric surface species, containing V 5+ and V…”
Section: Influence Of Support Materials On Catalytic Performancementioning
confidence: 98%